Ruminal and intestinal digestibility of some tropical legume forages - Khamseekhiew, B.; Liang, J.B.; Wong, C.C.; Jalan, Z.A. (Asian-Australasian Association of Animal Production Societies, 2001)
Two experiments were conducted to examine the degradation rates of 4 tropical legume forages in rumen and intestine of Kedah-Kelantan (KK) cattle. Three KK cattle, averaging 173 ± 17.15 kg each fitted with a permanent ruminal and a T-shaped duodenal cannulae were used. The cattle were fed a maintenance diet (1% DM of their body weight) composing of 60% oil palm frond (OFF) pellet and 40% of a legume mixture of Arachis pintoi (AP) and Leucaena throughout the study. The overall DM and CP degradabilities in the rumen for Gliricidia sepium (GS) and AP were significantly higher than those for Leucaena leucocephala-Bahru (LB) and Leucaena leucocephala-Rendang (LR). This implies that LB and LR would have higher dietary protein flows into the intestine for the more efficient enzymatic digestion. However, the results of the present study suggested only limited proportions of the ruminai undegraded protein in the Leucaenas were digested in the intestine.